A Framework for Understanding the Evasion of Host Immunity by Candida Biofilms - Garcia-Perez, Josselyn E.; Mathé, Lotte; Humblet-Baron, Stephanie; Braem, Annabel; Lagrou, Katrien; Van Dijck, Patrick; Liston, Adrian (Frontiers in Immunology, 2018)
Candida biofilms are a major cause of nosocomial morbidity and mortality. The mechanism by which Candida biofilms evade the immune system remain unknown. In this perspective, we develop a theoretical framework of the three, not mutually exclusive, models which could explain biofilm evasion of host immunity. First, biofilms may exhibit properties of immunological silence, preventing immune activation. Second, biofilms may produce immune deviating factors, converting effective immunity into ineffective immunity. Third, biofilms may resist host immunity which would otherwise be effective. Using a murine subcutaneous biofilm model, we found that mice infected with biofilms developed sterilizing immunity effective when challenged with yeast-form Candida. Despite the induction of effective anti-Candida immunity, no spontaneous clearance of the biofilm was observed. These results support the immune resistance model of biofilm immune evasion, and demonstrate an asymmetric relationship between the host and biofilms, with biofilms eliciting effective immune responses yet being resistant to immunological clearance.